A stabilized finite element method for Stream function vorticity formulation of Navier-Stokes equations - Mohamed Abdelwahed; Nejmeddine Chorfi; Maatoug Hassine (Electronic Journal of Differential Equations, 2017)
We the solvability of the two-dimensional stream function-vorticity formulation of the Navier-Stokes equations. We use the time discretization and the method of characteristics order one for solving a quasi-Stokes system that we discretize by a piecewise continuous finite element method. A stabilization technique is used to overcome the loss of optimal error estimate. Finally a parallel numerical algorithm is presented and tested.